2020
DOI: 10.1186/s12885-020-07392-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factor for short term postoperative cough after thyroidectomy

Abstract: Background The prevalence of potential risk factors for postoperative cough after thyroidectomy remain unknown. The current study aimed to research postoperative cough in patients undergoing thyroid surgery prospectively. Methods Adult patients who underwent primary thyroid surgery were selected prospectively. Data regarding age, sex, BMI, pathology and surgical procedure were collected and analyzed. The Leicester Cugh Questionnaire (LCQ) was required to be completed by all patients before operation, 2 weeks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Our study showed that sex was not a factor associated with postoperative cough, which is consistent with the results of Xie et al [ 10 ]. There also was no significant difference about postoperative cough between females and males after thyroidectomy [ 24 ]. This may be related to the bias in patient inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that sex was not a factor associated with postoperative cough, which is consistent with the results of Xie et al [ 10 ]. There also was no significant difference about postoperative cough between females and males after thyroidectomy [ 24 ]. This may be related to the bias in patient inclusion.…”
Section: Discussionmentioning
confidence: 99%